Is Treat-to-target in Lupus Nephritis Realistic in Clinical Practice? - Mok, Chi C. (Current Rheumatology Reviews, 2019)
The Treat-to-Target (T2T) principle has been advocated in a number of inflammatory and non-inflammatory medical illnesses. Tight control of disease activity has been shown to improve the outcome of rheumatoid arthritis and psoriatic arthritis as compared to the conventional approach. However, whether T2T can be applied to patients with lupus nephritis is still under emerging discussion. Treatment of lupus nephritis should target at inducing and maintaining remission of the kidney inflammation so as to preserve renal function and improve survival in the longterm. However, there is no universal agreement on the definition of remission or low disease activity state of nephritis, as well as the time points for switching of therapies. Moreover, despite the availability of objective parameters for monitoring such as proteinuria and urinary sediments, differentiation between ongoing activity and damage in some patients with persistent urinary abnormalities remains difficult without a renal biopsy. A large number of serum and urinary biomarkers have been tested in lupus nephritis but none of them have been validated for routine clinical use. In real life practice, therapeutic options for lupus nephritis are limited. As patients with lupus nephritis are more prone to infective complications, tight disease control with aggressive immunosuppressive therapies may have safety concern. Not until the feasibility, efficacy, safety and cost-effectiveness of T2T in lupus nephritis is confirmed by comparative trials, this approach should not be routinely recommended with the current treatment armamentarium and monitoring regimes.
Keywords: immunosuppressive